A REPRESENTAÇÃO MIDIÁTICA DO PROFESSOR BRASILEIRO NAS PÁGINAS BRANCAS E AMARELAS DE VEJA E CARTACAPITAL - Frederico, Eloiza de Oliveira (2014)
This research is based on a psychosocial perspective of the Social Representations Theory, systematized by Serge Moscovici and Denise Jodelet, that aims to analyze how weekly news magazines (Veja and Carta Capital) represent themes related to teachers. This issue, from a theoretical point of view, justifies itself in the light of medias fundamental part in the contemporary society as caster and producer of information. Journalistic products that were published for a year in the countrys biggest and most important weekly news magazine (Veja) were raised, as well as in Carta Capital, about the issue teacher and its variants. The only criteria for the selection of the texts was that they should verse about the Brazilian teacher, regardless of their stage of academic development, including reports, interviews and/or opinionated articles. This investigation covers, still as a theoretical-methodological resource, the concept of media representation as elaborated by Sary Calonge CALONGE. Seventy nine journalistic products were analyzed between January 2012 and January 2013, that indicated that teachers are practically an invisible being in journalistic scripts and articles from these communication establishments. To talk about education the teacher must be from the economic area. In the few times that hes mentioned or even appears with some emphasis, the use of stereotypes and cliches is notable, which points to the existence of a naturalized speech by the media in which the teacher is sometimes pointed as villain and sometimes as victim of the circumstances that permeate the current educational situation in Brazil.